Committee for the Relief of Distressed Seamen: correspondence from the Admiralty in 1818–19. Issue 975 (31st January 2007) - Cook, G C
Abstract : The Seamen's Hospital Society, which was to become a great Victorian charity, with the object of caring for both the physical and spiritual health of seafarers (most merchant seamen) in the Port of London, was founded at a meeting on 8 March 1821. However, it is not widely known that it had a temporary predecessor— The Committee for the Relief of Distressed (Destitute) Seamen . Ready cooperation was received from the Admiralty in most of its affairs, but "disposal" of many of these "redundant" mariners proved to be a somewhat difficult matter.